The Oldest Inventory of St. Nicolas of Bari - Levy, Brooks Emmons (Traditio, 1965)
The oldest published inventory of the collegial church of St. Nicolas in Bari dates from A. D. 1313, and testifies to the interest taken by Charles II of Anjou in the basilica, his regia cappella. In 1296 Charles donated to St. Nicolas a number of liturgical ornaments and service-books; in 1304 he required that its thesaurarius (a canon of the basilica appointed by himself) make periodic inventories in quadruplicate of the objects under his care. As a result, detailed inventories of St. Ncolas' treasure begin in the early fourteenth century and continue, though with considerable lacunae, to the nineteenth. Most of these inventories have been published in whole or in part; they show that the basilica once had a large collection of liturgical objects and codices, particularly in the Angevin period. It is clear from the first inventory that the nucleus of this collection was Charles II's donation, which still forms the most impressive part of St. Nicolas' now depleted treasure; accordingly Charles has been considered the ‘founder’ of the treasury.